GmERF13 mediates salt inhibition of nodulation through interacting with GmLBD16a in soybean - Xinfang Zhu; Xifeng Yan; Weijun Li; Mengyue Zhang; Junchen Leng; Qianqian Yu; Like Liu; Dawei Xue; Dajian Zhang; Zhaojun Ding (Nature Communications)
Abstract While the genetic regulation of nodule formation has been well explored, the molecular mechanisms by which abiotic stresses, such as salt stress, impede nodule formation remain largely elusive. Here, we identify four APETALA2/Ethylene Responsive Factor (AP2/ERF) transcription factors, GmERF13s, that are induced by salt stress and play key roles in salt-repressed nodulation. Loss of GmERF13 function increases nodule density, while its overexpression suppresses nodulation. Moreover, salt stress-inhibited nodule formation is greatly attenuated in GmERF13 loss-of-function mutants, whereas it becomes more pronounced when GmERF13 is overexpressed. Furthermore, GmERF13s can interact with Lateral Organ Boundaries Domain 16 (GmLBD16a), which attenuates GmLBD16a’s binding capacity on Expansin17c (GmEXP17c) promoter. Additionally, salt-induced GmERF13s expression relies on abscisic acid signaling, with direct promotion facilitated by GmABI5, illustrating their direct involvement in enhancing GmERF13s expression. Collectively, our study reveals a molecular mechanism by which salt stress impedes nodulation through the GmERF13-GmLBD16a-GmEXP17 module in soybean.